Disaster Management Response Guidelines for Departments of Orthopaedic Surgery. Issue 1 (5th January 2016) - Born, Christopher; Mamczak, Christiaan; Pagenkopf, Eric; McAndrew, Mark; Richardson, Mark; Teague, David; Wolinsky, Philip; Monchik, Keith
Abstract : Complacency and lack of preparation are major barriers to an effective disaster response. Leadership assignments and departmental organization for a response should be outlined in advance. Response rehearsal and after-action reviews allow for thoughtful change to a response plan. Hospital disaster alert notification systems should be standardized and should be understood. Communication systems used in a disaster should have redundancy. A department's response plan must be integrated into the overall hospital plan. Large casualty volumes require appropriate triage and resource allocation. Response provider emotional and health support is an important consideration.